Granular jamming based controllable organ design for abdominal palpation - He, L; Herzig, N; De Lusignan, S; Nanayakkara, T (Institute of Electrical and Electronics Engineers, 2018)
Medical manikins play an essential role in the training process of physicians. Currently, most available simulators for abdominal palpation training do not contain controllable organs for dynamic simulations. In this paper, we present a soft robotics controllable liver that can simulate various liver diseases and symptoms for effective and realistic palpation training. The tumors in the liver model are designed based on granular jamming with positive pressure, which converts the fluid-like impalpable particles to a solid-like tumor state by applying low positive pressure on the membrane. Through inflation, the tumor size, liver stiffness, and liver size can be controlled from normal liver state to various abnormalities including enlarged liver, cirrhotic liver, and multiple cancerous and malignant tumors. Mechanical tests have been conducted in the study to evaluate the liver design and the role of positive pressure granular jamming in tumor simulations.